Research on the oxidation sequence of Ni-Al-Pt alloy by combining experiments and thermodynamic calculations - Na Ta; Lijun Zhang; Qin Li (AIMS Materials Science)
In this paper, a comprehensive study on 1373 K high-temperature oxidation behaviors in a Ni-20 at.% Al-5 at.% Pt system was performed by coupling experimental investigations with CALPHAD (CALculation of PHAse Diagram) calculations. The discussion was expanded to include the effects of chemical concentrations on the degradation mechanism of thermally grown oxide layers during oxidation at 1373 K. A step-by-step oxidation procedure was established: first, aluminum oxide grows on the underside, followed by nickel oxide, which fully develops and penetrates the original aluminum oxide. The formation of NiO leads to aluminum enrichment and nickel depletion; once the concentration of Al achieves a threshold, θ-Al2O3 transforms into α-Al2O3, forming a tight structure. At this point, Al diffusion toward the exterior predominates, followed by the inward diffusion of O. The diffusion of Ni is gradually restricted by the establishment of the α-Al2O3 layer. When Al is not enough, Al2O3 combines with NiO to develop NiAl2O4. Nickel segregation may also occur during subsequent oxidation at the oxide layer/matrix alloy boundary. Small voids are likely to form due to the merging of the vacancies caused by the unbalanced diffusion of Al toward the Al2O3 layer and the opposite diffusion of Ni, resulting in significant peeling failure. Additionally, Pt has a beneficial effect by forming a thinner oxide scale that is more resistant to spallation.